Convective transport of formaldehyde to the upper troposphere and lower stratosphere and associated scavenging in thunderstorms over the central United States during the 2012 DC3 study. Issue 12 (24th June 2016) - Fried, A.; Barth, M.C.; Bela, M.; Weibring, P.; Richter, D.; Walega, J.; Li, Y.; Pickering, K.; Apel, E.; Hornbrook, R.; Hills, A.; Riemer, D. D.; et al.
Abstract: We have developed semi‐independent methods for determining CH2 O scavenging efficiencies (SEs) during strong midlatitude convection over the western, south‐central Great Plains, and southeastern regions of the United States during the 2012 Deep Convective Clouds and Chemistry (DC3) Study. The Weather Research and Forecasting model coupled with chemistry (WRF‐Chem) was employed to simulate one DC3 case to provide an independent approach of estimating SEs and the opportunity to study CH2 O retention in ice when liquid drops freeze. Measurements of CH2 O in storm inflow and outflow were acquired on board the NASA DC‐8 and the NSF/National Center for Atmospheric Research Gulfstream V (GV) aircraft employing cross‐calibrated infrared absorption spectrometers. This study also relied heavily on the nonreactive tracers i ‐/ n ‐butane and i ‐/ n ‐pentane measured on both aircraft in determining lateral entrainment rates during convection as well as their ratios to ensure that inflow and outflow air masses did not have different origins. Of the five storm cases studied, the various tracer measurements showed that the inflow and outflow from four storms were coherently related. The combined average of the various approaches from these storms yield remarkably consistent CH2 O scavenging efficiency percentages of: 54% ± 3% for 29 May; 54% ± 6% for 6 June; 58% ± 13% for 11 June; and 41 ± 4% for 22 June. The WRF‐Chem SE result of 53% for 29 May was achieved only when assuming complete CH2 O degassing from ice. Further analysis indicated that proper selection of corresponding inflow and outflow time segments is more important than the particular mixing model employed. Key Points: Obtained remarkably consistent CH2 O scavenging efficiencies of 41 to 58% in all but one storm Six of seven different methods produced the same result on one storm within a 7% range Erroneous scavenging efficiencies result when inflow and outflow are not coherently related